Simulation and validation of charge carrier drift in pixelated microstructured semiconductor neutron detectors - Laramore, Diego (Kansas State University, 2020)
A semiconductor neutron imaging device is proposed (X-MSND) based on high efficiency, Micro-structured Semiconductor Neutron Detector (MSNDs) bump bonded onto a Timepix pixelated readout chip. The device serves as a combined neutron and photon imager with a 256x256 pixel array, using per-pixel time-over-threshold (ToT) energy deposition. The X-MSND design has produced thermal neutron detection efficiency of 14%, significantly greater than the theoretical maximum of less than 5% for planar devices. Simulated pixel clusters showed similar qualitative characteristics as planar neutron sensitive Timepix hybrid detectors. A workflow for simulating the semiconductor physics, ionization by radiation, and charge carrier transport for micro-structured sensors in general has been devised and described in this work. The simulation workflow began by steady state initial conditions of the X-MSND PIN diode sensor at full bias using COMSOL Multiphysics. This simulation step served the combined purpose of providing the necessary electric field solutions used in charge transport, and provided necessary design and operating parameters for device fabrication. Radiation transport code Geant4 was used to simulate the radiation detection characteristics of the sensor: thermal neutron detection efficiency, energy deposition per detection event, and the location of the ionized charge cloud per interaction are all calculated at this step. Dassault SolidWorks was used to generate Computer-Assisted Drafting (CAD) models of the full micro-structured device geometry, which was then converted and imported into a format that can be interpreted by Geant4 for the radiation transport. Geant4 can then interface directly with a modified version of Allpix^2 to perform charge carrier drift over the entire X-MSND geometry. Fabricated X-MSND devices were tested and evaluated at Kansas State University (KSU), and were found capable of producing high quality radiographs with both X-rays and neutrons. The fabrication of functioning X-MSND/Timepix assemblies was a collaborative effort among several research groups at KSU, domestic and international industrial partners, and international research groups. Fabrication of the X-MSND sensors was performed largely by Radiation Detection Technologies, Inc., with parametric design support from the Radiological System Integration Laboratory (RSIL) and Radiological Engineering Analysis Laboratory (REAL). The processes used in the production of X-MSND sensors are conventional micro-electro-mechanical system (MEMS) photolithography techniques; spin-on deposition and ultraviolet development of photoresist, metal lift-off, and wet etching of silicon are all used over the course of fabrication, and are described in detail. The Electronics Design Laboratory (EDL) of Kansas State University assisted in the design of custom printed circuit boards to which the X-MSND/Timepix assemblies are mounted. External to facilities located at KSU, various industrial manufacturing partners who specialize in Very Large Scale Integration (VLSI) and micro-fabrication assembly processes were also contracted to perform the specialized assembly processes required in assembling the full X-MSND/Timepix systems.
Keywords: Pixelated Detector; Timepix; Bimodal Radiography; Micro-fabrication; Semiconductor Simulation